A new simple scoring system for prediction of success and complication rates in pediatric percutaneous nephrolithotomy: stone-kidney size score. Issue 1 (February 2019) - Çitamak, B.; Dogan, H.S.; Ceylan, T.; Hazir, B.; Bilen, C.Y.; Sahin, A.; Tekgül, S.
Summary: Introduction: Nomograms and scoring systems designed for predicting the success of percutaneous nephrolithotomy (PCNL) in adults are currently available. However, no scoring system currently exists primarily for predicting PCNL success in children. Objectives: The objective of this study was to develop a scoring system to predict the stone-free and complication rates by using pre-operative parameters. Study design: A retrospective analysis was conducted on data from 434 renal units belonging to patients with kidney stones who underwent PCNL between 1997 and 2017. Renal stone index was calculated by dividing the length of the stone along its longest axis by the length of the kidney along its longest axis. Guy's Stone scores, S.T.O.N.E scores, and CROES scores for adults were calculated by filling in the variables for each patient. Factors that predicted success and complications were examined by univariate and multivariate analyses. Results: Mean age was 8.3 (1–16) years, and male to female ratio was 236:165. When stone-free patients were compared with other patients, there was a statistically significant difference in the average stone/kidney index (SKI) value (stone size/kidney size on longitudinal axis) (0.266 vs 0.339, P  < 0.001). In multivariate analysis, factors that predicted success were the SKI and number of stones. A newly developed scoring scale, the stone-kidney score (SKS), combined scores for both the SKI and the number of stones into one value. A minimum total SKS score was 2, and a maximum total SKS score was 4. Success rates for SKS scores of 2, 3, and 4 were 86.4%, 73%, and 62.9% ( P  < 0.001), respectively. Complication rates for SKS scores of 2, 3, and 4 were 13%, 22.1%, and 23.8%, respectively. Discussion: The new scoring system has only two variables (number of stones and SKI) and three risk groups. An SKS score is easier to use and calculate. An SKI value can be simply calculated on any imaging modality by dividing the length of the stone along its longest axis by the length of the kidney along its longest axis. As in the new scoring system, the SKI value combined with the number of stones is useful in predicting stone-free rates after PCNL. Conclusion: When evaluated together, the SKI and presence of multiple stones may predict stone-free rates pre-operatively. The SKS is an individual-specific method that can be easily used in pediatric clinical practice. Further studies are required to develop and standardize this method. Table Distribution of success and complication rates regarding SKS. Table Total score Success rate Bleeding Complications without bleeding Total complications 2 86.4% 7.1% 5.9% 13% 3 73% 13.1% 8.2% 22.1% 4 62.9% 12.6% 10.5% 23.8%   P =0.001 P  = 0.112 P  = 0.140 P =0.014 SKS, stone-kidney score.